Effect of Sb content on anisotropic magnetoresistance in a (Ga, Mn)(As, Sb) ferromagnetic semiconductor thin film. Issue 19 (8th April 2019) - Wang, Wenjie; Chen, Jing; Deng, Jiajun; Che, Jiantao; Hu, Bing; Cheng, Xin
Abstract : The effect of Sb content on the in-plane anisotropic magnetoresistance (AMR) of the quaternary ferromagnetic semiconductor (Ga, Mn)(As, Sb) was investigated. Abstract : The effect of Sb content on the in-plane anisotropic magnetoresistance (AMR) of the quaternary ferromagnetic semiconductor (Ga, Mn)(As, Sb) was investigated. The results showed that the strain increased with Sb content, but the hole density was found to fluctuate. Dominant cubic and uniaxial symmetries were observed for the current along the [110] crystalline direction. The dependence of the symmetry on the Sb content was demonstrated for the longitudinal AMR, which mainly results from the alteration of the local stain relaxation and the hole density. A phenomenological analysis showed that the variation of the AMR coefficients is a good explanation for the observed experimental results.